Peranan Koperasi Sebagai Penyedia Kebutuhan Nelayan di Kabupaten Barru - Djumran Yusuf; Amiluddin Amiluddin; Jumaraini Jumraini (Jurnal IPTEKS Pemanfaatan Sumberdaya Perikanan, 2014)
This research aims to study the cooperative roles as fisherman’s need provider (a Case study at Budi Bahari Cooperative, Barru Regency).  The major Problem that was interesting to discuss was how the cooperative roles as fisherman’s need to fulfill specifically as a capital, equipment and daily needs provider, and to affect the consumer purchase decision at Budi Bahari Cooperative. This study used a case study to assess the Budi Bahari Cooperative performance related to fishermen’s catch and daily life.  Purposive sampling method was used with respondents from Budi Bahari’s Cooperative staffs and five fisherman groups (25 people). Data were collected through direct interview for all respondents and were analyzed using chi square method. Results showed that Budi Bahari Cooperative gave sizeable role by loan capital, supply equipment and daily needs of cooperative’s members who work as a fisherman. Hence, the purchase decision was not influenced by the price, and but it was affected by product type, and goods distribution